2020
DOI: 10.1016/j.cmet.2019.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a LIF-Responsive, Replication-Competent Subpopulation of Human β Cells

Abstract: Highlights d Single-cell profiling identifies genes induced in proliferating b cells d Activation of the LIF pathway induces proliferation of human b cells d LIFR + b cells represent a subpopulation of transcriptionally distinct b cells d STAT3 and CEBPD are targets of LIF and regulators of b-cell proliferation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 58 publications
3
34
1
Order By: Relevance
“…In addition, Lifr (LIF receptor) was only slightly expressed in clusters 2 and 10 (SFigure 11), the  cell subgroups that were exclusively from normal mice. However, Lifr expression was not detected in cluster 14 either, indicating that the highly proliferative subgroup of  cells identified in this study is not likely associated with LIF responsiveness, different from what was previously reported (42). In our study, we found that cluster 14 had high expression of Hmgb1 and Hmgb2 (SFigure 10), indicating that these two DNA binding proteins might initiate a transcriptional program that gives rises to the identity of this group of cells.…”
Section: Discussioncontrasting
confidence: 93%
“…In addition, Lifr (LIF receptor) was only slightly expressed in clusters 2 and 10 (SFigure 11), the  cell subgroups that were exclusively from normal mice. However, Lifr expression was not detected in cluster 14 either, indicating that the highly proliferative subgroup of  cells identified in this study is not likely associated with LIF responsiveness, different from what was previously reported (42). In our study, we found that cluster 14 had high expression of Hmgb1 and Hmgb2 (SFigure 10), indicating that these two DNA binding proteins might initiate a transcriptional program that gives rises to the identity of this group of cells.…”
Section: Discussioncontrasting
confidence: 93%
“…This study also established that human fetal pancreatic C-peptide + /KI67 + cells expressed higher frequencies of CD9 + compared to the C-peptide + /KI67cells, confirming the higher proliferative status of the CD9 + fraction in vivo. As mentioned previously, recent findings from the Melton lab identified YAP as one factor that could drive proliferation of b-like cells while reducing their maturation when up-regulated during their differentiation (32,48). This group had also identified that WNT signaling was found in replicating epithelial progenitor cells and is down-regulated in mature endocrine-like cells (53).…”
Section: Caveats Linked To Promoting Proliferation During Hpsc Differmentioning
confidence: 79%
“…Screening primary human b-cells for mitogens that had been previously identified to initiate proliferation in rodent b-cells revealed that many factors were unable to initiate significant replication, with the dual-specificity tyrosine phosphorylation regulated kinase 1A (DYRK1A)-inhibiting compound harmine being the only mitogen that induced significantly increased replication with treatment (31). Indeed, harmine is unique in that it has been repeatedly reported in the literature to induce bcell and other pancreatic cell replication (32)(33)(34)(35)(36)(37). Differing effects on b-cell replication through shared signaling mechanisms between rodent and human b-cells may be due to additional cellular factors that inhibit proliferation, such as the high accumulation of p16 in adult human b-cells (38)(39)(40).…”
Section: Comparison Of B-cell Proliferation Between Rodents and Humansmentioning
confidence: 99%
See 2 more Smart Citations